Foldable Structures Adapted From Tessellation Origami With High Degree Of Freedom - Chai, Chen Chu (2018)
Geometrical shape of folded structure is closely related to origami especially the tessellation origami. Tessellation origami which has flexible folding mechanism provides a folded configuration with facetted surface as a result from repeated folding pattern. Flexible folding mechanism is an under constraint system due to its high degree-of-freedom. The flexibility of folding mechanism is controlled by the fold angle imposed on the actuators. Currently available method of folding simulation was found to be not able to simulate tessellation origami with high degree-of-freedom. Hence, this research is conducted with the aim to develop the procedure for simulation of tessellation origami with high-degree of freedom through the control of actuators. The first objective of this research is the identification of geometric considerations for folding pattern with flexible mechanism. 40 numbers of actual tessellation origami were first re-produced to study the relation between the geometric characteristics of the corresponding mountain valley pattern on the flexibility of the physical behaviour of the replica model. Geometric considerations affecting the folding mechanism were identified by investigating the local degree-of-freedom of the crease line pattern through the use of a procedure for the computation of local degree-of-freedom of the mechanism proposed in this research. The second objective is the development of an alternative simulation approach using generative algorithm. A generative modeling tool using visual programming editor Grasshopper® which provides a more realistic simulation tool by incorporating the kinematic property of the origami was developed. The last objective of this research is the determination of the folded configuration in relation to the control system for actuators. Six tessellation origami models consisting of three variations of Miura-ori, Russo’s Optical Illusion, Yoshimura and Ron Resch pattern were selected to investigate the transformation under different paths using the generative modeling tool. Transformations under different combination of the distance between actuator and curvature of an imaginary curve connecting all actuators have yielded a wide variety of folded configurations with non-synchonised local folding pattern for the six tessellation origami models.